ANALISIS PADA KEMATIAN AKIBAT PENYAKIT JANTUNG DI RUMAH SAKIT UMUM PUSAT H. ADAM MALIK MEDAN MENGGUNAKAN POISSON RIDGE REGRESSION (PRR) - Yolandini Eka Putri; Rina Filia Sari; Rima Aprilia (Math Educa Journal, 2022)
Heart disease is a general term for all diseases that attack the heart organ. Death from the heart at the H. Adam Malik Central General Hospital was recorded to have a fairly high number. The purpose of this study was to determine the use of the Poisson Ridge Regression (PRR) method on the results of the analysis of deaths from heart disease at H. Adam Malik Central General Hospital Medan. PRR is a method that is generally used to estimate the regression of count data, and is very sensitive to multicollinearity. In this study, PRR was used to analyze deaths from heart disease in the presence of multicollinearity cases. The result shows that the estimated parameter of the PRR model is slightly different from the estimation of the Poisson regression model where the estimated value of the variable for patients with heart failure (X1) = 0,030751, the estimated value for patients with congenital heart disease (X2) = -0,002125, the estimated value for patients with heart disease ischemia (X3) = -0, 003085 and the estimated value of hypertension sufferers (X4) = 0,009689. The conclusion is that of the four variables, two of which have a positive influence on death from heart disease, namely patients with heart failure and patients with hypertension. This means that the more people with heart failure and hypertension, the more deaths from heart disease.